Being voiceless: a review on patient communication in intensive care unit - Mohamed Ariffin, Suzilawati; Mohamed Ludin, Salizar; Mohd Arifin, Siti Roshaidai (2019)
Introduction: When speech is integral, the interactions will come out automatically; but if the speech is damaged, even the basic conversation seems to be difficult to handle. While providing nursing care to the patients, nurses must appreciate the uniqueness of each patient and try to promote health and well-being as much as they can. To do so, the nurses must help the patient to fulfill their need and the best way to so is by properly listen to the patient ‘voice'. Objective: To appraise the available evidence that study about voiceless among patient in the Intensive Care Unit. Design: A literature review. Data sources: Six online databases namely CINAHL, ProQuest, ScienceDirect, Clinical key, Scopus, and Ovid Medline were searched. Review methods: Relevant studies were identified using combined approaches of electronic database search and hand searching journals. Results: Twelve 12 studies met the inclusion criteria. Few topics summarized from the studies are a general view of nurse-patient communication in the Intensive Care Unit, barrier and factor that limit nurse-patient communication, consequences of voicelessness, and the method to overcome voicelessness. Conclusion: Supports from nurses are needed by patient especially when they are mechanically ventilated for them to make sense of their condition and trying to cope with it.